Avaliação comportamental do processamento auditivo em crianças aos cinco anos de idade - Santos, Fabíola Andréa Andrade dos (2012)
It is increasing number of children who presents deaf behaviors even though their hearing level is into the normal range. These behaviors characterize symptom of the Auditory Processing Disorder which may affect speech and learning development. So it is important the early identification of changes in the auditory processing, especially at preschool age, in order to eliminate and minimize future impairments. Purpose: to describe the auditory processing characteristics of a cohort of five-year-old children. Materials and Methods: a cross-sectional clinic quantitative and exploratory survey carried out with 305 children at the age of five, who are part of a 2005 birth cohort. Behavior and socioeconomic aspects and background history of diseases were searched as well as previous pregnancies and health conditions developed during pregnancy, completion of prenatal, data collection regarding delivery and birth. The evaluation was made in private and public schools through special tests: Sound Localization (SL), Non Verbal Sequential Memory (NVSM), Verbal Sequential Memory (VSM) and Cochlear Palpebral Reflex (CPR). The Chi-square test and Pearson s correlation coefficient were selected for results and risk factors analysis and correlation. Results: While 97% of the children passed in the SL test and 60.4% in the VSM test, 85.5% failed in the NVSM test. Concerning CPR, presence was observed in 99.7% of the sample and no significant difference was verified. Furthermore, no crucial difference was perceived in the results of the tests applied in the sexes and in the schools part of the study. In the quantitative analysis of correct answers, only 11.8% had right answers in all the four tests, however, there was no significant difference. Statistically significant correlation was found between the SL test and the 1st minute Apgar risk factors (p=0.09) and Cephalic Perimeter (p=0.018). Correlation was also observed with the following tests: NVSM and the variable government assistance (p=0.046), and poverty index (p=0.003) and VSM for the variable government assistance (p=0.00) and poverty income (p=0.003). In addition, statistically significant correlation between mother s education and the NVSM (p=0.019) and VSM (p=0.000) tests were found. Conclusion: It was verify a large prevalence of the alteration on auditory behavior on this sample; the adequate Cochlear Palpebral Reflex (CPR) and sound localization were present and Non Verbal Sequential Memory and Verbal Sequential Memory were changed in a significant number of children; the inappropriate conditions of pregnancy and childbirth contributed in improvement of alteration in sound localization. Lower socioeconomic conditions and low maternal education cause negatively influence on development on non-verbal sequential memory and verbal sequential memory skills.